THE UNCERTAINTY PROBLEM IN THEORY AND PRACTICE HIGHER SCHOOL - Семиченко, В.; Артюшина, K. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article deals with the problem of uncertainty as an integral attribute of modern man's life. The importance of forming tolerance to uncertainty as an important means of organizing a person's life path is revealed. Manifestations of situations of uncertainty in student life are analyzed. Empirical data are presented that reveal the features of the development of uncertainty tolerance in future professionals. It is argued that uncertainty is an integral attribute of the life of a human being in the modern world, the basic features of which are multidimensionality, polysystems, continuous variability, the presence of many objective and subjective conflicts, the need to make decisions with insufficient information. The factors that complicate the subjective process of decision making and action are specified: - lack of clear knowledge of the nature of the phenomena that must be involved to overcome uncertainty; lack of clear evaluation criteria for the expediency and potential effectiveness of the available methods and directions for resolving the situation; a person's lack of a clear idea of ​​the results he wants to obtain; lack of clear awareness of their own resources, their sufficiency to resolve the situation and achieve the intended ones. It has been proven that in a situation of uncertainty there can be two main types of emotional experiences: positive (interest, curiosity) and negative (fear or anxiety), as well as different coping strategies: stimulating activity and blocking activity. This was the basis for introducing such concepts as "tolerant / intolerant personality", "tolerance / intolerance to uncertainty". The results of the empirical study revealed: a) insufficient readiness of a considerable part of the interviewed students to overcome situations of insignificance, especially in the sphere of interpersonal relations; b) the presence in one third of students of signs of professional uncertainty in the context of professional choice; c) limited ability of students to produce various ways of solving uncertainty situations.